Do treatment patterns alter beliefs cancer patients hold regarding oral oncolytic agents?. Issue 3 (11th January 2018) - Sikorskii, Alla; Given, Charles W.; Given, Barbara A.; Vachon, Eric; Marshall, Victoria; Krauss, John C.; Banik, Asish; Majumder, Atreyee
Abstract: Objective: Cancer patients, particularly those prescribed with oral oncolytic medications, face treatment side effects and temporary and permanent stoppages of treatment. This research examines how events during treatment affect patients' beliefs regarding oral oncolytic medications. Methods: A total of 272 cancer patients initiating 1 of 28 oral oncolytic agents were followed for 12 weeks. Assessments of Beliefs About Medications Questionnaire, symptoms, physical function, and depression measures were performed during telephone interviews at intake (medication start) and 4, 8, and 12 weeks. Electronic medical record audits identified dates of temporary and permanent medication stoppages. Linear mixed‐effects models were used for longitudinal analyses of the Beliefs About Medications Questionnaire scores in relation to patient characteristics, symptom severity, and medication stoppages. Results: Over the initial 12 weeks, beliefs about the necessity of oral medications have increased, concerns have decreased, and interference of medications with daily lives has increased. Permanent stoppage of a medication predicted significant declines in beliefs about its necessity over time. Male patients, those less educated, those reporting higher symptom severity, and those experiencing temporary stoppages had greater concerns. Interference of medications with daily life was higher for males, increased with higher symptom severity, and differed by drug category. Conclusions: Patients' beliefs in the necessity of their oral medication were affected only by a permanent drug stoppage. Symptom severity, education, and patient sex affected patients' beliefs about their concerns with their medications and the interference medications posed for their daily lives. Interventions may need to target the distinct dimensions of beliefs during treatment with oral oncolytic agents.